Réponses

2012-05-27T15:24:41+02:00

a. 4x = -13.2

x = -3,3


b.4-x = -13.2

x = 9,2


c.x/4 = -13.2


d.27-8x = 33

-8x = 6

-x = 0,75


e.9-2x = -5x+8

-2x+5x = 8-9

3x = -1

x = 0,33333...


f.-2(3x-8) = -9+5x

-6x-5x = 16-9

-11x = 7

-x = 0,63636363636364 

Meilleure réponse !
2012-05-27T16:18:05+02:00

a. 4x = -13.2

4x/4=-13.2/4

x = -3,3


b.4-x = -13.2

-4+4-x=-13.2-4

-x*-1=9.2*-1

x = -9,2


c.x/4 = -13.2

x/4*4 = -13.2*4

x = 52,8


d.27-8x = 33

-27+27-8x=33-27

-8x/8=6/8

-x*(-1) = 0,75*(-1)

x = -0,75


e.9-2x = -5x+8

+2x-8+9-2x=-5x+8+2x-8

-3x/3=1/3

-x*(-1) =  0,33333...*(-1)

x =(environ egale)= -0.333


f.-2(3x-8) = -9+5x

-2*3x+(-2)*(-8) = -9+5x

-5x-16-6x+16 = -9+5x-5x-16

x = 25


jespére que sa t'aura aidée d'avantage.